2023
DOI: 10.1371/journal.pone.0283810
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intrinsic and extrinsic drivers influence the quantity and quality components of seed dispersal effectiveness in the rare shrub Lindera subcoriacea

Abstract: Information about seed dispersal effectiveness (SDE) for plant species of conservation concern is rarely available to inform management strategies and actions. For Lindera subcoriacea (bog spicebush, Lauraceae), a rare endemic dioecious shrub of the southeastern United States, we examined the influence of two intrinsic and five extrinsic drivers on the number and proportion of seeds either dispersed, or predated pre- and post-dispersal. The number of seeds dispersed characterizes the quantitative component of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 120 publications
(183 reference statements)
0
6
0
Order By: Relevance
“…There are still additional considerations to be addressed when modeling L. subcoriacea seed dispersal, including various intrinsic and extrinsic drivers, and use of allometrically estimated versus observed avian parameters. For example, Hohmann et al [59] found that understory cover affected the magnitude of pre-dispersal seed predation and individual height affected L. subcoriacea SDE Q , but neither of these drivers were captured within our current model. The effects of vegetation management, such as prescribed fire, can also affect the availability of L. subcoriacea and other fleshy fruits in time and space [51,116] and influence L. subcoriacea SDE Q [59], but this variation was not included in our experiments.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…There are still additional considerations to be addressed when modeling L. subcoriacea seed dispersal, including various intrinsic and extrinsic drivers, and use of allometrically estimated versus observed avian parameters. For example, Hohmann et al [59] found that understory cover affected the magnitude of pre-dispersal seed predation and individual height affected L. subcoriacea SDE Q , but neither of these drivers were captured within our current model. The effects of vegetation management, such as prescribed fire, can also affect the availability of L. subcoriacea and other fleshy fruits in time and space [51,116] and influence L. subcoriacea SDE Q [59], but this variation was not included in our experiments.…”
Section: Discussionmentioning
confidence: 71%
“…Lindera subcoriacea is a rare, dioecious, avian-dispersed [59] shrub that inhabits several wooded wetland communities of the southeastern U.S. [51]. Small, isolated populations of L. subcoriacea have been identified in seven southeastern states [50].…”
Section: Study System and Speciesmentioning
confidence: 99%
See 3 more Smart Citations